THE UTILIZATION OF DIGITAL PLATFORMS IN ONLINE LEARNING: EFL STUDENTS’ PERSPECTIVES - Ira Irzawati (University of Kuningan, 2021)
The purpose of this research was to investigate the EFL students’ perspectives toward the utilization of digital platforms in online learning. Learning Management System, WhatsApp, and Google Meet are the digital platforms used in the online learning of this research. This descriptive research involved 79 students from three different faculties of a private university in Palembang that selected through purposive sampling technique. The data were collected by administrating questionnaires and interviews to the participants via Google Form and WhatsApp Chat. Collecting, classifying, and describing were a set of data analysis procedures used by the researcher. The results revealed that the students perceived the use of the digital platforms in EFL learning positively. The students believed that learning through utilizing the digital platforms had brought positive impacts that lead to the enhancement of their English achievement. Using multi-digital platforms provided an opportunity to experience a more dynamic learning atmosphere that boosts their skill progress and motivation.Keywords: digital platforms; online learning; EFL; students’ perspective